Integration of Information and Communication Technology in Islamic Education Management Overview of Smart Learning and Smart Building Study at Islamic Digital Boarding College (IDBC) Sukoharjo - Akhmad Akromusyuhada; Adi Fachrudin; Andriyani Andriyani; Masyitoh; Saiful Bahri (International Journal of Integrative Sciences, 2023)
To be able realization all of this, this research focuses on understanding: (1) Islamic Education Management, (2) Smart Learning Educational Facilities and Infrastructure that relate of  Smart Buildings, (3) Integration of Information and Communication Technology. This research is qualitative research with a phenomenological approach. Data collection techniques: (1) observation, (2) interviews, (3) documentation studies, (4) internet searching. Data analysis use data processing techniques, NVivo analysis and data interpretation as well as theory validation through triangulation. The results of the research show that: (1) In general, Islamic Digital Boarding College (IDBC) is an Islamic boarding school educational institute which based on the integration of information and communication technology in the education management process carried out, IDBC (Islamic Digital Boarding College) is a 21st century education model for manners & IT Campus to give birth for a generation of Technopreneur Da'i whose can give for servants of Allah and Khalifah. (2) Management of Islamic education includes functions, principles, objectives and characteristics. Management of Islamic Education is not much different from management in generally. Planning, Organizing, Actuating, and Controlling must be based on the Al Quran and Al Hadith to achieve the goals of Islamic education effectively and efficiently